Direct cytogenetic study of chorionic samples of the arrested pregnancy tissues according to the Regional Reproductive Center materials - N. V. Avramenko; D. Ye. Barkovsky; I. V. Semenenko; N. A. Kalabuchova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2015)
Aim. Detection of chromosomal aberrations in patients during spontaneous abortion.